Excretion of the Polymyxin Derivative NAB739 in Murine Urine - Vaara, Martti; Vaara, Timo; Kuka, Janis; Sevostjanovs, Eduards; Grinberga, Solveiga; Dambrova, Maija; Liepinsh, Edgars (Antibiotics (Basel), 2020)
Extremely multiresistant strains of Enterobacteriaceae are emerging and spreading at a worrisome pace. Polymyxins are used as the last-resort therapy against such strains, in spite of their nephrotoxicity. We have previously shown that novel polymyxin derivatives NAB739 and NAB815 are less nephrotoxic in cynomolgus monkeys than polymyxin B and are therapeutic in murine Escherichia coli pyelonephritis at doses only one-tenth of that needed for polymyxin B. Here we evaluated whether the increased efficacy is due to increased excretion of NAB739 in urine. Mice were treated with NAB739 and polymyxin B four times subcutaneously at doses of 0.25, 0.5, 1, 2, and 4 mg/kg. In plasma, a clear dose–response relationship was observed. The linearity of Cmax with the dose was 0.9987 for NAB739 and 0.975 for polymyxin B. After administration of NAB739 at a dose of 0.25 mg/kg, its plasma concentrations at all tested time points were above 0.5 µg/mL while after administration at a dose of 0.5 mg/kg its plasma concentrations exceeded 1 µg/mL. The Cmax of NAB739 in plasma was up to 1.5-times higher after single (first) administration and up to two-times higher after the last administration when compared to polymyxin B. Polymyxin B was not detected in urine samples even when administered at 4 mg/kg. In contrast, the concentration of NAB739 in urine after single administration at a dose of 0.25 mg/kg was above 1 µg/mL and after administration of 0.5 mg/kg its average urine concentration exceeded 2 µg/mL. At the NAB739 dose of 4 mg/kg, the urinary concentrations were higher than 35 µg/mL. These differences explain our previous finding that NAB739 is much more efficacious than polymyxin B in the therapy of murine E. coli pyelonephritis.